Suara Ekofeminis dalam Narasi Pedesaan di Jawa: Kajian Gender dan Alam dalam Novel Ronggeng Dukuh Paruk Karya Ahmad Tohari - Abd. Wafir Ramadhani; Efendi, Agik Nur (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the relationship between women and nature in Ahmad Tohari’s novel Ronggeng Dukuh Paruk through Susan Griffin’s ecofeminist perspective. The research is grounded in the view that women and nature are often positioned as objects of patriarchal domination, yet at the same time hold the potential for resistance and ecological recovery. The aim of this study is to describe four central aspects of Griffin’s thought, namely (1) women as guardians of nature, (2) the feminization of nature and the naturalization of women, (3) roar as a symbol of resistance, and (4) the ethics of care and the interconnectedness between women and the environment. The method employed is descriptive qualitative with reading-note techniques and interpretative analysis of the novel’s narrative. The findings show that the character Srintil represents both the female body and nature silenced by social structures, yet still preserves spiritual strength, ecological awareness, and a form of silent resistance. Srintil’s inner bond with the Dukuh Paruk landscape demonstrates the role of women as agents in restoring human–nature relations through the integration of cultural, spiritual, and ecological values. These findings reaffirm the relevance of ecofeminism as a critical perspective in Indonesian literary studies as well as a futurological foundation for envisioning a more just, empathetic, and sustainable society. Thus, the novel not only presents cultural and ecological narratives, but also provides insights into the strategic role of women in socio-ecological transformation.Penelitian ini menelaah keterkaitan antara perempuan dan alam dalam novel Ronggeng Dukuh Paruk karya Ahmad Tohari melalui pendekatan ekofeminisme Susan Griffin. Penelitian ini didasarkan pada pandangan bahwa perempuan dan alam kerap menjadi objek dominasi patriarki, tetapi pada saat yang sama memiliki potensi resistensi dan pemulihan ekologi. Tujuan penelitian adalah untuk mendeskripsikan empat aspek utama pemikiran Susan Griffin, yaitu (1) perempuan sebagai penjaga alam, (2) feminisasi alam dan naturalisasi perempuan, (3) roar sebagai simbol perlawanan, dan (4) etika kepedulian serta keterhubungan perempuan dengan lingkungan. Metode yang digunakan adalah deskriptif kualitatif dengan teknik baca-catat dan analisis interpretatif terhadap narasi dalam novel. Hasil penelitian menunjukkan bahwa tokoh Srintil merepresentasikan tubuh perempuan sekaligus alam yang dibungkam oleh struktur sosial, namun tetap menyimpan kekuatan spiritual, kesadaran ekologi, dan perlawanan senyap. Kedekatan batin Srintil dengan lanskap Dukuh Paruk memperlihatkan perempuan berperan sebagai agen pemulih relasi manusia dengan alam melalui perpaduan nilai budaya, spiritual, dan ekologi. Temuan ini menegaskan relevansi ekofeminisme sebagai perspektif kritis dalam studi sastra Indonesia serta sebagai pijakan futurologis untuk membayangkan masyarakat yang lebih adil, empatik, dan berkelanjutan. Dengan demikian, novel ini tidak hanya memuat narasi kultural dan ekologis, tetapi juga membuka wawasan mengenai peran strategis perempuan dalam transformasi sosial-ekologi.